Translational research: Current status, challenges and future strategies in Nepal - Parajuli, Surya B.; Bhattarai, P; KC, Heera (Nepalese Heart Journal, 2018)
The concept of translational research is emerging around the globe. The practice of clinical care, health promotion and health care delivery system need to be evidence based. Translational research is the utmost solution to generate evidence and implement the scientific findings. Now the time has come to conduct translational research in Nepal to generate our own evidence and to integrate it into the policy of new federal health system. The objective of this review article was to identify status, challenges and future strategies of translational research in Nepal.